Molecular toxicological alterations in the mouse hearts induced by sub‐chronic thiazolidinedione drugs administration. (25th May 2021) - Jarrar, Yazun Bashir; Jarrar, Qais; Abaalkhail, Sara J.; Moh'd Kalloush, Hanin; Naser, Wisam; Zihlif, Malek; Al Shhab, Mohammad; El Madani, Abdulla; Jamous, Yahya; Lee, Su‐Jun
Abstract: Thiazolidinediones are well‐known anti‐diabetic drugs. However, they are not widely used due to their cardiotoxic effects. Therefore, in this study, we aimed to determine the molecular toxicological alterations induced in the mouse hearts after thiazolidinedione administration. Balb/c mice received doses clinically equivalent to those given to humans of the most commonly used thiazolidinediones, pioglitazone, and rosiglitazone for 30 days. After that, RNA samples were isolated from the hearts. The mRNA expression of cytochrome (cyp) p450 genes that synthesize the cardiotoxic 20‐hydroxyeicosatetraenoic acid (20‐HETE) in addition to 92 cardiotoxicity biomarker genes were analyzed using quantitative polymerase chain reaction array technique. The analysis demonstrated that thiazolidinediones caused a significant upregulation ( p  < 0.5) of the mRNA expression of cyp1a1, cyp4a12, itpr1, ccl7, ccr1, and b2 m genes. In addition, thiazolidinediones caused a significant ( p  < 0.05) downregulation of the mRNA expression of adra2a, bsn, col15a1, fosl1, Il6, bpifa1, plau, and reg3b genes. The most affected gene was itpr1 gene, which was upregulated by pioglitazone and rosiglitazone by sevenfold and 3.5‐fold, respectively. In addition, pioglitazone caused significant upregulation of ( p  < 0.05) hamp, ppbp, psma2, sik1, timp1, and ucp1 genes, which were not affected significantly ( p  > 0.05) by rosiglitazone administration. In conclusion, this study showed that thiazolidinediones induce toxicological molecular alterations in the mouse hearts, such as the induction of cyp450s that synthesize 20‐HETE, chemokine activation, inflammatory responses, blood clotting, and oxidative stress. These findings may help us understand the mechanism of cardiotoxicity involved in thiazolidinedione administration.